HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY ANALYTICAL METHOD VALIDATION FOR GLUTARALDEHYDE AND BENZALKONIUM CHLORIDE IN DISINFECTANTS - Maggadani, Baitha Palanggatan; ., Harmita; Isfadhila, Maizura (International Journal of Applied Pharmaceutics, 2018)
Objective: The aim of this study was to produce a selective, accurate, and faster high-performance liquid chromatography (HPLC) analytical method for benzalkonium chloride and glutaraldehyde in disinfectants using ultraviolet (UV)-visible detection. Methods: Glutaraldehyde has no chromophore, so it was first derivatized using 2,4 dinitro phenylhydrazine. Acetonitrile:water (75:25) was used as the mobile phase for glutaraldehyde and acetonitrile-acetate pH 4 (75:25) for benzalkonium chloride, both at a flow rate of 1.2 mL/min. The optimized assay was validated with respect to accuracy, precision, linearity, selectivity, limit of quantitation (LOQ), and limit of detection (LOD). Results: The method was linear for benzalkonium chloride, with correlation coefficient of 0.9995, LOD of 14.55 ppm, and LOQ of 48.51 ppm. The correlation coefficient for glutaraldehyde was 0.9995, with LOD of 0.49 ppm and LOQ of 1.64 ppm. Accuracy was between 98% and 102%, and precision was below 2% for both the tests. Conclusion: The HPLC analytical method for benzalkonium chloride and glutaraldehyde in disinfectants using UV-visible detection in this research was successful to produce a selective, accurate, and faster method.